Insights on Public Health Professionals Non-technical Skills in an Emergency Response (Multi-Team System) Environment - Black, Andrew; Brown, Olivia; Utunen, Heini; Gamhewage, Gaya; Gore, Julie (Frontiers in Psychology, 2022)
This paper provides practitioner and academic insights into the importance of examining non-technical skills in a multiteam system emergency response. The case of public health professionals is highlighted, illustrated with unique qualitative field data which focused upon the use of non-technical skills at a meso level of analysis. Results reflected the importance of context upon the multiteam system and highlighted seven non-technical skills used by public health professionals to support an effective response. Recommendations for future research and implications for practice are noted for this hard to access professional group, located within emerging advances in the scientific inquiry of complex and increasingly evident, multi-team systems.